The Service Quality and Brand Trust Toward Purchase Decisions the Mediating Role of Customer Satisfaction : A Conceptual Paper - Fahmi Renaldy Azzam; Arry Widodo; Anita Silvianita; Nurafni Rubiyanti (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research analyzes the relationship between service quality and brand trust through customer satisfaction regarding purchase decisions with a sample of Bandung people who know and have bought Crocs products at Shopee. This research method is Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach, using the help of SmartPLS 3.0 software. This research shows an influence between service quality and brand trust on purchase decisions through customer satisfaction. Customer satisfaction mediates between service quality, brand trust, and purchase decisions. This research has several implications for companies that pay attention to service quality and build brand trust to create customer satisfaction, which impacts increasing purchase decisions